Proposed Tariff Legislation since 1883 - Perry, O. H. (Quarterly Journal of Economics, 1887)
Proposed Tariff Legislation since 1883 Get access O. H. Perry O. H. Perry Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 2, Issue 1, October 1887, Pages 69–78, https://doi.org/10.2307/1879351 Published: 01 October 1887